Pembangunan teknik kawalan pencemaran menggunakan pembakar berbahan api cecair dengan aliran berpusar - Mohd. Jaafar, Mohammad Nazri; Mustafa, Azeman; Musa, Hamidon; Senawi, Yusof; Wan Omar, Wan Zaidi; Abdul Majid, Kamsani; Mohamad Shaiful Ashrul, Ishak (Faculty of Mechanical Engineering, 2005)
A liquid fuel burner system with curved radial air swirler vane angles with swirl number (SN) variation between 0.046 to 1.911 has been investigated. A combustor with single central fuel nozzle is used to determine the effect of swirl number in emissions formation especially NOX and other emissions such as CO, UHc and CO2. Swirling flow affect the recirculation zone provides the aerodynamics blockage to stabilise the flame, improved mixing between air and fuel and formation of emissions. NOX reduction of more than 26% was obtained for the swirl number of 1.427 compared to 0.046. In order to achieve enhanced recirculation zone and better control of mixing process, a swirler consisting of an orifice plate at the outlet of radial swirler was introduced. The purpose of orifice plate insertion was to create the swirler pressure loss at the swirler outlet so that the swirler outlet shear layer turbulence was maximized to assist in mixing of air and fuel. This technique showed reduction of about 22% of NOX emissions were obtained compared to non-orifice assistance.